2002
DOI: 10.1124/dmd.30.12.1320
|View full text |Cite
|
Sign up to set email alerts
|

Major Phase I Biotransformation Pathways of Trichostatin A in Rat Hepatocytes and in Rat and Human Liver Microsomes

Abstract: ABSTRACT:Phase I biotransformation of Trichostatin A (TSA), a histone deacetylase inhibitor with promising antifibrotic and antitumoral properties, was investigated in rat and human liver microsomes and in suspensions of rat hepatocytes. TSA (50 M) was readily and completely metabolized by rat hepatocytes in suspension (2 ؋

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…TSA is one of the most potent HDAC inhibitors that exerts its effects at very low concentrations (nanomolar), but its poor bioavailability in vivo, due to an extensive biotransformation or instability, makes its use a continuing topic of controversy (20,(24)(25)(26). Unfortunately, none of the numerous HDAC inhibitors is specific for single isoforms of HDAC, but few drugs show preferences for groups of HDACs or for single HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…TSA is one of the most potent HDAC inhibitors that exerts its effects at very low concentrations (nanomolar), but its poor bioavailability in vivo, due to an extensive biotransformation or instability, makes its use a continuing topic of controversy (20,(24)(25)(26). Unfortunately, none of the numerous HDAC inhibitors is specific for single isoforms of HDAC, but few drugs show preferences for groups of HDACs or for single HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…Ten years ago, Niki and colleagues 10,11 introduced an HDI as a candidate to preserve a quiescent HSC phenotype in vitro; however, the role of individual HDACs was not addressed, because the broad spectrum inhibitor TSA was used to inhibit the in vitro HSC activation. Because of TSA's limited use in vivo 20,27 we set out to test the influence of the more selective class I HDI VPA 15,16 on the mouse model of CCl 4 -induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of TSA's limited use in vivo, 20 the influence of the HDI VPA on the mouse model of CCl 4 -induced liver fibrosis was tested because of its preference toward class I HDACs 15,21 and its documented use in mouse models. 18,22 Mice were treated with CCl 4 for 4 weeks with or without VPA in their drinking water.…”
Section: Vpa Partly Inhibits CCL 4 -Induced Fibrosismentioning
confidence: 99%
“…Xenobiotic biotransformation is generally recognized as a key determinant of the efficacy and toxicity of a potential new drug (Li, 2001;Elaut et al, 2002). However, little information on the biotransformation of HA-based HDACi is available in the current literature, and attempts to optimize their metabolic properties have been scarce.…”
mentioning
confidence: 99%
“…However, little information on the biotransformation of HA-based HDACi is available in the current literature, and attempts to optimize their metabolic properties have been scarce. We previously showed that 50 M TSA is completely inactivated within 40 min upon incubation with rat hepatocyte suspensions (Elaut et al, 2002). Another group (Sanderson et al, 2004) subsequently reported a half-life of 6.3 min upon peritoneal administration of TSA (0.5 mg ⅐ kg) to mice.…”
mentioning
confidence: 99%